Systemic sclerosis: severe pulmonary arterial hypertension and pericardial effusion at diagnosis - Moniz, Patricia (BMJ Case Rep, 2018)
A 51-year-old female patient with a recent hospital admission reported to the emergency room (ER) with progressive worsening of fatigue, dyspnoea and chest discomfort. She had been recently admitted and discharged with the diagnosis of pericarditis and medicated with non-steroidal anti-inflammatory drugs and diuretics. She returned to the ER with persisting symptoms. Echocardiography was repeated and showed signs of elevated right ventricular systolic pressure and a slightly increased moderate/severe pericardial effusion without signs of cardiac tamponade. The patient was admitted and further evaluation confirmed an underlying case of advanced systemic sclerosis with skin, vascular, pulmonary and cardiac involvement. The patient was referred to specialised consults in autoimmune pathology and pulmonary arterial hypertension. She was started on bosentan and corticosteroids, presenting a favourable clinical evolution although symptoms of exertional dyspnoea persist.